Odpowiedź :
Odpowiedź:
1/2 * (3x-1) - 1/3 * (4y-7) =2
1/4 * (3y-6) - 1/6 * (5-x) = -17/12
1/2 * 3x - 1/2 * 1 - 1/3 * 4y + 1/3 * 7 = 2
1/4 * 3y - 1/4 * 6 - 1/6 * 5 +1/6 *x = - 17/12
3/2x - 1/2 - 4/3y + 7/3 = 2
3/4y - 6/4 - 5/6 + 1/6x = - 17/12
3/2x - 4/3y = 2 + 1/2 - 7/3
1/6x + 3/4y = - 17/12 + 6/4 + 5/6
3/2x - 4/3y = 2 + 3/6 - 14/6
1/6x + 3/4y = - 17/12 + 18/12 + 10/12
3/2x - 4/3y = 2 - 11/6
1/6x + 3/4y = 11/12
3/2x - 4/3y = 1/6
1/6x + 3/4y = 11/12
18/12x - 16/12y = 2/12
2/12x + 9/12y = 11/12 / * ( - 9)
18/12 x - 16/12y = 2/12
- 18/12x - 81/12y = - 99/12
dodajemy stronami
18/12x - 18/12x - 16/12y - 81/12y = 2/12 - 99/12
- 97/12y = - 97/12 / * ( - 12/97)
y = 1
podstawiamy y do pierwszego równania
18/12x - 16/12 * 1 = 2/12
18/12x = 2/12 + 16/12
18/12x = 18/12 / * 12/18
x = 1
y = 1
x = 1
spr
1/2 * (3 * 1 - 1) - 1/3 * (4 * 1 - 7) = 2
1/4 * (3 * 1 - 6) - 1/6 * (5 - 1) = - 17/12
1/2 * 2 - 1/3 * ( - 3) = 2
1/4 * ( - 3) - 1/6 * 4 = - 17/12
1 + 1 = 2
- 3/4 - 4/6 = - 17/12
2 = 2
- 9/12 - 8/12 = - 17/12
2 = 2
- 17/12 = - 17/12
Szczegółowe wyjaśnienie: